2018
DOI: 10.1186/s13068-018-1204-y
|View full text |Cite
|
Sign up to set email alerts
|

Delignification of corncob via combined hydrodynamic cavitation and enzymatic pretreatment: process optimization by response surface methodology

Abstract: BackgroundRenewable liquid biofuel production will reduce crude oil import of India. To displace the huge quantity of fossil fuels used for energy production, this research was focused on utilization of unexploited low-cost agricultural residues for biofuel production. Corncobs are a byproduct of corn processing industry, and till now it is not utilized for biofuel production, eventhough it has high lignocellulosic concent. In this study, combined hydrodynamic cavitation and enzymatic (HCE) method was evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(22 citation statements)
references
References 48 publications
3
15
0
2
Order By: Relevance
“…In the present study, the enzymatic pretreatment of CCB in an HCR-LccH resulted in a significant reduction in lignin (54.1%) and hemicellulose (6.57%), and increase in cellulose (24.26%), which confirms our previous finding [10]. With the pre-treated CCB, at 5% solid loading rate, we attained a saccharification efficiency of 54.59% using partially purified cellulase (40 U mL −1 ) of CMCPS1 at 96 h. Cellulase, a complex of three different enzymes, acts in synergism and a cooperative association, producing substrates for each other [17,40].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, the enzymatic pretreatment of CCB in an HCR-LccH resulted in a significant reduction in lignin (54.1%) and hemicellulose (6.57%), and increase in cellulose (24.26%), which confirms our previous finding [10]. With the pre-treated CCB, at 5% solid loading rate, we attained a saccharification efficiency of 54.59% using partially purified cellulase (40 U mL −1 ) of CMCPS1 at 96 h. Cellulase, a complex of three different enzymes, acts in synergism and a cooperative association, producing substrates for each other [17,40].…”
Section: Discussionsupporting
confidence: 93%
“…Several studies have suggested combined pretreatment methods due to their better delignification efficiency [9]. More recently, hydrodynamic cavitation technology coupled with an oxidative enzyme (laccase 6.5 U of Trametes versicolor) was one of the successfully employed LCB pretreatment [10]. Highly reactive radicals (H-and OH-) generated due to the cavitational effect degrade lignin moieties, although not optimal for targeting specific end products [11].…”
Section: Introductionmentioning
confidence: 99%
“…Hsiao, Kuo, Hsieh, and Hou () reported that 10 times higher biodiesel oil conversion rates were observed for waste cooking oil samples treated with a HPH than those samples treated conventionally by heating in water bath at same reaction rates. Other successful research using HC for waste management include delignification of corn cob (a by‐product of corn industry; Thangavelu, Desikan, Taran, & Uthandi, ), extraction of pectin from peels of pomelo (Guo et al, ) and food waste anaerobic digestion (Tran, ). It is safe to view HC as a promising and energy saving technology in processing food industrial waste.…”
Section: Application Of Hcmentioning
confidence: 99%
“…Orifice plates [22,24,35,[37][38][39], Venturi tubes [40,41], and high-pressure nozzles [42][43][44][45][46][47][48] are examples of static HC elements [49]. While they are cheap and simple devices, but they require powerful feeding pumps due to the high pressure loss needed to generate HC in these types of devices.…”
Section: Hc Reactors: Technical Aspectsmentioning
confidence: 99%
“…The cavitational yield and energy consumption were less than those of other pre-treatment methods. However, the orifice plate was obstructed with a high corncob-slurry biomass loading rate (>6.75%) [24]. Similarly, 16 g of corn stover powder (<250 µm) was added in 400 mL of the 0.4 M Na 2 CO 3 /0.6 M H 2 O 2 solutions, and the slurry was then circulated for 1 h at 30 • C within a Venturi tube HCR (40 mm length; 3.6 mm internal diameter; 1.8 mm throat diameter).…”
Section: Delignification Of Lignocellulosic Biomassmentioning
confidence: 99%